2021
DOI: 10.1002/smll.202007073
|View full text |Cite
|
Sign up to set email alerts
|

Nonspherical Metal‐Based Nanoarchitectures: Synthesis and Impact of Size, Shape, and Composition on Their Biological Activity

Abstract: Metal‐based nanoentities, apart from being indispensable research tools, have found extensive use in the industrial and biomedical arena. Because their biological impacts are governed by factors such as size, shape, and composition, such issues must be taken into account when these materials are incorporated into multi‐component ensembles for clinical applications. The size and shape (rods, wires, sheets, tubes, and cages) of metallic nanostructures influence cell viability by virtue of their varied geometry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 358 publications
(358 reference statements)
0
15
0
Order By: Relevance
“…This nano (sub-micron) particles provide higher surface area of bioactive glass and in a result more binding sites for cell adhesion and bone formation 3 . The size of nanoparticles has direct effect on their biological activity 30 . Panda et al, reported that nano-scale environment is favorable for stem cell attachment, propagation and differentiation through an increase in reciprocal interactions between extracellular matrix and cells 31 .…”
Section: Discussionmentioning
confidence: 99%
“…This nano (sub-micron) particles provide higher surface area of bioactive glass and in a result more binding sites for cell adhesion and bone formation 3 . The size of nanoparticles has direct effect on their biological activity 30 . Panda et al, reported that nano-scale environment is favorable for stem cell attachment, propagation and differentiation through an increase in reciprocal interactions between extracellular matrix and cells 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The ability of nanomedications to remain undetected by the mononuclear phagocytic system, and to interact with the complex biological environment of cells and tissues, are crucial prerequisites for their effective clinical translation in vivo. [ 9,10 ] Accordingly, the design of nanoplatforms with an active targeting capability and high affinity for target cells has gained increasing attention. This may be achieved by functionalizing the nanomaterials with specific targeting ligands such as antibodies, peptides, aptamers, or even small molecules that are capable of interacting with receptors overexpressed in pathological tissues.…”
Section: Introductionmentioning
confidence: 99%
“…[184][185][186] Nanoparticles interact with various active biomolecules after coming in contact with body fluids. [187,188] Protein adsorption is the first event occurring after nanomaterials (e.g., MBGs) meet protein-containing biological fluids (e.g., blood plasma) loading for the formation of a dynamic surface layer of proteins on pristine nanoparticles, called protein corona, playing a vital role in the interaction between the nanoparticles and the body. [189] Protein corona formation is influenced by the nanoparticles' physicochemical characteristics, proteins properties, and surrounding media bioenvironment (Figure 16).…”
Section: Mbg and Proteins Interactions: Protein Coronamentioning
confidence: 99%